TNI Neutrality in General Elections: Analysis of Army Family Voting Rights in Magelang - Aisyahwara, Fillia Galuh; Fahadayna, Adhi Cahya (Politika: Jurnal Ilmu Politik, 2024)
The neutrality regulations of the Indonesian National Army (TNI) enable them to be able to maintain the Spirit of Reform. The reformation mandate requires the army to be neutral in the General Elections in Indonesia. This writing aims to find out the participation of the Indonesian army family in the general election, especially in the 2019 presidential election in a case study in Magelang City, and the extent to which TNI family understands the neutrality of TNI and their participation in the activities of the Presidential General Election in 2019. The method applied in this research uses the qualitative descriptive type and the case study type based on interviews and observation. The research results show that army families in Magelang City already know the rules regarding TNI neutrality during elections. As civil society, the TNI family also exercised their right to vote, and no one participated as a success team or party officer. In this case, the TNI family is given the freedom to choose without any interference from TNI members. Based on the research that has been carried out it can be concluded that there is a need to increase awareness and conditions when the related person is faced with the situation as head of the family and a member of the TNI in order to to maintain the spirit of the constitution.